PENGARUH PENGGUNAAN LKPD TERHADAP MOTIVASI BELAJAR MATEMATIKA PADA MATERI FUNGSI KUADRAT KELAS IX MTsN 11 AGAM - Putri Indah Febriani; Gema Hista Medika; Fauzal Fauzal (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to explore the positive effect of using Learner Worksheets (LKPD) on motivation to learn mathematics on quadratic function material in class IX at MTsN 11 Agam. Math learning motivation is a key factor in improving students' academic performance and strengthening their understanding of complex mathematical concepts. This research is a quantitative descriptive research. The population in this study were ninth grade students at MTsN 11 Agam with a sample of 50 students. The collection technique used a Likert scale questionnaire by calculating the average percentage score of each indicator. The results of this study indicate that the use of LKPD on quadratic function material has a significant positive impact on students' motivation to learn mathematics. This confirms that LKPD can be an effective tool in triggering students' motivation to understand and master mathematical concepts, especially in material that is considered difficult such as quadratic functions. This is because there is an increase in the average learning motivation from before using LKPD of 58,60% to 78,30% after using LKPD. LKPD is also categorized as good for its feasibility as indicated by the average student response for each indicastor in the interval 70 < x ≤ 85. This research provides valuable insights into the important role of LKPD in increasing students' motivation to learn mathematics. The results of this study can be used as a foundation for the development of.